Recommendations for the Pharmacological Treatment of Osteoporosis – Update 2023 of the German Osteoporosis Guideline - Schmidmaier, Ralf; Hadji, Peyman; Kern, Peter; Drey, Michael; Jakob, Franz; Thomasius, Friederike (Osteologie, 2023)
Aim The German osteoporosis guideline was updated on the basis of a systematic literature review and through a structured consensus process by an interdisciplinary, international (Germany, Austria, Switzerland) expert group representing the 20 member societies of the Joint Osteological Association (DVO) and patient advocacy organizations (BfO). This manuscript summarizes the changes in the German osteoporosis guideline with regard to pharmacological interventions and offers pragmatic pathways for implementation.Method Systematic literature search and structured consensus building according to AWMF regulations.Results The sclerostin antibody romosozumab was adopted into the guideline. In addition, the effectiveness of teriparatide was re-evaluated. For both bone anabolic agents evidence from randomized trials underlined a superiority over oral bisphosphonates with regard to fracture risk reduction. Between the antiresorptive treatments, differences regarding superiority/inferiority could only be shown with respect to surrogate parameters, not with regard to fractures. Data about the duration of treatment of all available drugs is limited. All non-bisphosphonate treatments require follow-up treatment.Conclusion An individualized treatment concept should be developed in a shared decision process, including a bone anabolic-first strategy in high-risk patients. Recommendations on treatment duration, drug holidays and sequential strategies should be considered.Ziel Auf Basis eines systematischen Literaturreviews und durch strukturierte Konsensfindung einer interdisziplinären, internationalen (Deutschland, Österreich, Schweiz) Expertengruppe, welche die 20 Mitgliedgesellschaften des Dachverbandes Osteologie (DVO) und die Patientenvertretung Bundesselbsthilfeverband für Osteoporose e.V. (BfO) repräsentiert, wurde die deutschsprachige S3-Osteoporoseleitlinie aktualisiert. In diesem Artikel werden die Neuerungen des Kapitels zur medikamentösen Therapie vorgestellt und Möglichkeiten zum Transfer in die tägliche Praxis diskutiert.Methode Systematische Literaturrecherche und strukturierte Konsensfindung gemäß AWMF-Regelwerk.Ergebnisse Neu aufgenommen wurde in die Leitlinie der Sklerostin Antikörper Romosozumab. Zudem erfolgte eine Neubewertung der Effektivität von Teriparatid. Für beide Osteoanabolika liegt Evidenz aus randomisierten, direkten Vergleichsstudien vor, die eine Überlegenheit gegenüber oralen Bisphosphonaten bezüglich Frakturrisikoreduktion zeigen. Innerhalb der Antiresorptiva konnten nur Unterschiede der Überlegenheit/Unterlegenheit bezüglich Surrogatparametern, nicht bezüglich Frakturen gezeigt werden. Die Daten zur Therapiedauer aller verfügbarer Medikamente sind limitiert. Nicht-Bisphosphonate erfordern eine Anschlusstherapie.Schlussfolgerung Es sollte partizipativ ein individuelles Therapiekonzept entwickelt werden; bei Hochrisikopatienten mit einer Osteoanabol-First-Strategie. Empfehlungen zur Therapiedauer, Therapiepausen und notwendigen Sequenzen sind zu beachten.
Keywords: Osteoporosis; guideline; drugs; treatment